Les démons étaient-ils vraiment le problème à Corinthe ? Un réexamen de 1 Co 10:20–22 - Patmore, Hector M. ca. 20./21. Jh. (2023)
A consensus of opinion exists among scholars that Paul appears to contradict himself in 1 Cor 10:17–22: on the one hand, he makes clear that idols have no existence beyond the material objects themselves ; on the other hand, he appears to warn the Corinthians that they are exposing themselves to a dangerous metaphysical reality, namely demons (i.e., evil supernatural beings), by taking part in pagan cults. This supposed non sequitur is generally resolved by claiming that Paul adheres to two Jewish traditions simultaneously. The Jewish witnesses, however, do not support such a conclusion. In fact, the Jewish sources offer an alternative solution to this supposed problem, namely that Paul uses the word δαιμόνια to designate foreign gods to which he attributes no metaphysical reality. In short, there are no demons involved. As such, he maintains a biblical position : even if the idols are nothing but wood and stone, idolatry is forbidden.
Keywords: Deuteronomy; Corinthians; Paul; δαιμόνιον; Demonology